2010
DOI: 10.1016/j.healthplace.2010.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The Scottish excess in mortality compared to the English and Welsh. Is it a country of residence or country of birth excess?

Abstract: Scotland has a higher mortality rate than England and Wales that is only partially explained by differences in socio-economic deprivation. Within Scotland those born in England and Wales have a lower mortality rate than the Scottish born. Within England and Wales, Scottish born immigrants have a higher mortality rate than those born in England and Wales. These results raise the question of whether the greater Scottish mortality is a country of birth rather than a country of residence excess. Our analysis, arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Much of this is explained by recent experiences of deindustrialisation, deprivation and poverty, the latter being root causes of poor health in all societies, not just Scotland 4,[8][9][10][11][12] . However, in addition, high levels of excess mortality -that is, higher mortality over and above that explained by differences in socioeconomic deprivation -have been observed for Scotland compared with England & Wales [13][14][15][16][17] , as well as for Glasgow compared with similar post-industrial UK cities such as Liverpool,…”
Section: Introductionmentioning
confidence: 99%
“…Much of this is explained by recent experiences of deindustrialisation, deprivation and poverty, the latter being root causes of poor health in all societies, not just Scotland 4,[8][9][10][11][12] . However, in addition, high levels of excess mortality -that is, higher mortality over and above that explained by differences in socioeconomic deprivation -have been observed for Scotland compared with England & Wales [13][14][15][16][17] , as well as for Glasgow compared with similar post-industrial UK cities such as Liverpool,…”
Section: Introductionmentioning
confidence: 99%
“…46 Popham found that English & Welsh born immigrants to Scotland live longer than native Scots, and that those born in Scotland who move to England & Wales do not live as long as those who were born and continue to live in England & Wales, despite emigrants reflecting the Carstairs deprivation distribution of the recipient nation. 48 This was confirmed by a similar study which examined the death rates of different immigrant groups in England & Wales which showed Scottish and Irish immigrants had higher death rates (32% higher for Scottish men and 36% higher for Scottish women). 49 This casts doubt on a healthy migrant effect being responsible for the higher mortality in Scotland.…”
Section: Evidencementioning
confidence: 62%
“…The migration studies detailed in the previous section which suggest that Glaswegian migrants to other parts of Scotland and Scottish migrants to other parts of the UK retain a higher risk of mortality, do provide some (natural) experimental evidence that either genetics, early environmental exposures or retained cultures play a consistent role. 48,52,53 The wide range of cause-specific mortality categories which are in excess in Scotland and Glasgow (including alcohol-related, drug-related, cardiovascular, stroke, suicide etc.) makes a genetic cause unlikely.…”
Section: Evidencementioning
confidence: 99%
“…The migration hypothesis posits that the country’s higher mortality could be explained by the emigration of a higher proportion of healthy individuals from Scotland than from other Western European regions. But the limited literature on the subject shows that Scottish migrants display mortality profiles in their country of destination that are similar to those of non-migrants remaining in Scotland, particularly in death rates from lung cancer and ischemic heart disease (Connolly et al 2011; Popham et al 2010). …”
Section: Introductionmentioning
confidence: 99%